Psychometric Analysis of the Sexual Machism Scale (EMS-12) in Colombian Caribbean university students - Alvarez Merlano, Nicolás (2023)
Machismo constitutes the belief of superiority of men over women that derives from sexual behaviors and encourages in male and female units’ risky patterns such as the lack of condom use during sexual intercourse, alcohol abuse and gender-based violence. In Colombia, research has analyzed instruments that measure related traits such as sexism and sexual roles, reducing those that report a propensity for machismo. Therefore, the present manuscript aims to generate evidence of the psychometric properties of the Sexual Machismo Scale (EMS-12, Díaz-Rodríguez et al. 2010). Using an instrumental and descriptive quantitative methodological apparatus, the instrument was evaluated in 351 undergraduate Colombian university students (Mean= 22.06, SD= 2.98) through an exploratory factor analysis (AFE) to examine the structure of the instrument and a confirmatory (TFA) to ratify the model originally proposed. The results revealed the one-dimensionality of the scale, with indicators of internal consistency and goodness of fit satisfactory (α = .87; ω = .87; TLI = .97; CFI=.98; GFI=.98; RMSEA=.08). In addition, a reduced version was proposed whose indices of reliability and goodness of fit limited in what was appropriate (α = .93; ω = .93; TLI= .98; CFI=.99; GFI=.99; RMSEA=.04.) concluding that EMS-12 and EMS-12R have indicators of reliability, construct validity that validate its application in the Colombian Caribbean university population.